Training on Diversification and Labeling of Honey Products in the Taman Kelulut Ayoh Ku Bee Farming Community - Suwartiningsih, Nurul; Irsalinda, Nursyiva; Wahyudi, Rofiul; Saputra, Jumadil; Abd Razak, Shamsul Bahri; Sugiyarto, Sugiyarto (Research Collaboration Community (Rescollacom), 2024)
Taman Kelulut Ayoh Ku Bee Farming Community in Pengkalan Gelap, Kuala Setiu, Terengganu, Malaysia, is a group of Trigona sp. honey beekeepers. which faces challenges related to the availability of packaging facilities for kelulut honey. This community service activity is important to provide education and training to improve packaging facilities through diversification and labeling on honey product. The activity was carried out offline on August 8-9th, 2023. The results of the activity showed that the training on diversifying honey product packaging increased the knowledge and skills of 92.5% of participants, while the training on labeling honey product packaging increased the knowledge and skills of 80% of participants. The solutions presented can increase the knowledge and skills of community members, motivate the enthusiasm of farmers, and increase the selling value of honey products produced by the Taman Kelulut Ayoh Ku Bee Farming Community